Aspek-Aspek Kunci dalam Perkembangan Anak pada Masa Usia Dini - Sumiati Wahyuni; Susi Susanti; Sutra Awaliyah Darfin; Nurwajah Nurwajah; Nova Rimadani; Novita Sari (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
Early childhood development has a very large influence on the formation of various aspects of their lives, such as cognitive, emotional, social, and physical abilities. During this period, children begin to develop basic skills that will affect their quality of life in the future. This study aims to explore various factors that influence early childhood growth and development through an analysis of five relevant studies from Indonesia. Through a qualitative analysis approach, it was found that appropriate stimulation from the environment, supportive social interactions, and effective parenting patterns play an important role in child development. These findings are expected to provide insight for parents and educators in creating an environment that supports optimal child growth and development.